2017
DOI: 10.3847/1538-3881/aa9750
|View full text |Cite
|
Sign up to set email alerts
|

MASTER OT J132104.04+560957.8: A Polar with Absorption–Emission Line Reversals

Abstract: We present time-resolved photometry and spectroscopy of the recently classified polar MASTER OT J132104.04+560957.8. The spectrum shows a smooth, non-thermal continuum at the time of maximum light, without any individually discernible cyclotron harmonics. Using homogeneous cyclotron modeling, we interpret this as cyclotron radiation whose individual harmonics have blended together, and on this basis, we loosely constrain the magnetic field strength to be less than ∼30 MG. In addition, for about one-tenth of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(46 citation statements)
references
References 17 publications
6
40
0
Order By: Relevance
“…Based on photometric observations, the system was tentatively identified as a non-eclipsing polar (Kato 2012). It was confirmed as a polar based on its spectral properties by Littlefield et al (2015Littlefield et al ( , 2018. Optical spectra showed strong hydrogen Balmer and strong He II 4686 Å emission lines, and a non-stellar continuum that decreased blueward of 5000 Å.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…Based on photometric observations, the system was tentatively identified as a non-eclipsing polar (Kato 2012). It was confirmed as a polar based on its spectral properties by Littlefield et al (2015Littlefield et al ( , 2018. Optical spectra showed strong hydrogen Balmer and strong He II 4686 Å emission lines, and a non-stellar continuum that decreased blueward of 5000 Å.…”
Section: Introductionmentioning
confidence: 80%
“…Radial velocities and time-resolved photometry showed periodic variability at a period of 91 min, identified as the orbital period. Interestingly, the medium-resolution spectra obtained by Littlefield et al (2018) showed emission/absorption line-reversals at certain phases of the binary. Long-term Catalina Real-time Sky Survey (Drake et al 2009) photometric observations revealed pronounced brightness variations during 2007 -2012 (Littlefield et al 2018).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…HU Aquarii ∆m = 0.2 mag (Schwope & Thinius 2014) and FL Ceti ∆m = 1.0-1.5 mag (Mason et al 2015). The non-eclipsing polar Master J132104+560957.8 displays dips in its light curves associated with emission-absorption line reversals (Littlefield et al 2018). Since pre-eclipse dips are common in polars and indicate the presence of an accretion stream, their absence at low accretion rates and presence at high rates as observed in CRTS J0350+3232 is strong support for our classification of CRTS J0350+3232 as a polar.…”
Section: Pre-eclipse Dip -Absorption By the Accretion Streammentioning
confidence: 99%
“…In recent studies, Littlefield et al (2018) used the homogeneous cyclotron-emission model of Chanmugam & Wagner (1979) and Wickramasinghe & Meggitt (1985) to constrain the magnetic field strength of the WD in MASTER J132104.04+560957.8 to be ∼30 MG. Most recently, Joshi et al (2020) detected cyclotron harmonics in the optical spectra of three AM Her systems: RX J0859.1+0537, RX J0749.1-0549 and RX J0649.8-0737, which led to the determination of the magnetic field strength of the WD to be within ∼50 MG.…”
Section: Introductionmentioning
confidence: 99%